Voices from the Second Republic of South Vietnam (1967-1975) - Taylor, Keith Weller (Studies on Southeast Asia, 2014)
This volume recovers the stories of those who strove to build a constitutional structure of representative government in South Vietnam during a war for survival with a totalitarian state